Characteristics of keratinocyte carcinomas in Hispanics compared to non‐Hispanic whites: A retrospective 5‐year study. Issue 1 (29th August 2019) - Cheng, Judy; Rajanala, Susruthi; Widjajahakim, Rafael; Maymone, Mayra B. C.; Vashi, Neelam A.
Abstract: Background: Hispanics are one of the fastest growing populations in the United States. Few studies have characterized the patterns of keratinocyte carcinoma presentation in Hispanics. Objective: The study aimed to compare the clinical and histologic characteristics of keratinocyte carcinomas in Hispanics and non‐Hispanic whites. Materials and Methods: A five‐year retrospective chart review was conducted at a single academic center to identify all histologically‐confirmed cases of keratinocyte carcinomas. Tumor characteristics were then compared between Hispanics and non‐Hispanic whites. Results: A total of 197 tumors were identified of which 76% occurred in non‐Hispanic whites and 24% in Hispanics. Tumor diameter was not larger and histologic subtype was not more aggressive in Hispanics compared to non‐Hispanic whites. Age of diagnosis of basal cell carcinoma was younger among Hispanics compared to non‐Hispanic whites ( P < .05). Conclusion: Hispanics were not more likely to present with more high‐risk keratinocyte carcinomas compared to non‐Hispanic whites in terms of tumor diameter, differentiation and subtype.